Reimagining the Self at Late-Career Transitions. (June 2015) - Onyura, Betty; Bohnen, John; Wasylenki, Don; Jarvis, Anna; Giblon, Barney; Hyland, Robert; Silver, Ivan; Leslie, Karen
<x xml:space="preserve">Abstract</x> Purpose There is scant empirical work exploring academic physicians' psychosocial adjustment during late-career transitions or on the factors that influence their retirement decisions. The authors examine these issues through the lens of sociopsychological identity theory, specifically examining how identity threat influences academic physicians' decisions about retirement. Method Participants were academic physicians at a Canadian medical school and were recruited via e-mail requests for clinical faculty interested in discussing late-career and retirement planning issues. Participants included 15 males and 6 females (N = 21; mean age = 63, standard deviation = 7.54), representing eight specialties (clinical and surgical). Data were collected in October and November 2012 via facilitated focus groups, which were digitally recorded, transcribed verbatim, and anonymized, then analyzed using thematic analysis. Results Four primary themes were identified: centrality of occupational identity, experiences of identity threat, experiences of aging in an indifferent system, and coping with late-career transitions. Identity threats were manifested in apprehensions about self-esteem after retirement, practice continuity, and clinical competence, as well as in a loss of meaning and belonging. These identity challenges influenced decisions on whether to retire. Organizational and system support was perceived as wanting. Coping strategies included reimagining and revaluing various aspects of the self through assimilating new activities and reprioritizing others. Conclusions Identity-related struggles are a significant feature of academic physicians' considerations about late-career transitions. Understanding these challenges, their antecedents, and their consequences can prepare faculty, and their institutions, to better manage late-career transitions. Individual- and institution-level implications are discussed.